Unraveling Ferroptosis: A New Frontier in Combating Renal Fibrosis and CKD Progression - Rui Jin; Yue Dai; Zheng Wang; Qinyang Hu; Cuntai Zhang; Hongyu Gao; Qi Yan (Biology)
Chronic kidney disease (CKD) is a global health concern caused by conditions such as hypertension, diabetes, hyperlipidemia, and chronic nephritis, leading to structural and functional kidney injury. Kidney fibrosis is a common outcome of CKD progression, with abnormal fatty acid oxidation (FAO) disrupting renal energy homeostasis and leading to functional impairments. This results in maladaptive repair mechanisms and the secretion of profibrotic factors, and exacerbates renal fibrosis. Understanding the molecular mechanisms of renal fibrosis is crucial for delaying CKD progression. Ferroptosis is a type of discovered an iron-dependent lipid peroxidation-regulated cell death. Notably, Ferroptosis contributes to tissue and organ fibrosis, which is correlated with the degree of renal fibrosis. This study aims to clarify the complex mechanisms of ferroptosis in renal parenchymal cells and explore how ferroptosis intervention may help alleviate renal fibrosis, particularly by addressing the gap in CKD mechanisms related to abnormal lipid metabolism under the ferroptosis context. The goal is to provide a new theoretical basis for clinically delaying CKD progression.